Accounting for the Response-Shift: Pre-Service Teacher-Efficacy Development in Immersive Learning - Mucherah, Winnie; Thomas, Kendra Edwards (International Journal of Humanities and Social Science Research, 2015)
This article compares the changes in efficacy of pre-service teachers in an immersive learning practicum and in a traditional practicum. It does not assume that pre-service teachers take the same pattern of development as in-service teachers because of the restructuring that must occur in an educational setting. The first study followed the development of 159 preservice teachers and found a significant interaction between the two groups across time in terms of teacher efficacy. The immersive group’s efficacy increased significantly more than the control group. The second study assessed the response-shift of pre-service teachers between their pretests and their retrospective pretests. As hypothesized, the difference between the pretest and the retrospective pretest was greater for the immersive group compared to the control group, indicating the power that immersive experiences has to recalibrate the concept of teacher-efficacy. Implications for pre-service teacher education are discussed.